Effects of Population Pressure on Forest Resources in Trabzon-Turkey and How to Conserve them - Sumayyah Alsharif Ali Alshaybani; Aydn, Mira (Zenodo, 2022)
ABSTRACT The high population thickness in urban zones has brought about an enormous scope modification of the environment in the urban fringe. Urbanization is a mind-boggling procedure of changing over urban fringe and rustic land to urban land utilizes and has caused different effects on ecosystem structure, function, and dynamics. n one hand, the high rate of urbanization causes high density in settlement restricted zones of cities, then again, it costs increments to society because of the subsequent unplanned and uncontrolled urbanization and land use with the skirts, particularly in the urban fringe of natural habitat/landscape pieces and the defiled utilization of urban territories without considering natural law or the ecological balance. Suburban, urban fringe, and provincial advancement are the main source of biodiversity misfortune and natural asset degradation in Trabzon region. Forests used to be the main field of enthusiasm for provincial communities, however, now they pull in the consideration of urbanites as well. The forestthe advertising is significant as forests secure water assets, preserve the soil and increment its productivity, give positive impacts on climate and health as a rule, and can be utilized for recreation and tourist purposes. Our review aims at evaluating how the current rapid urbanization process in Trabzon influences forests. Urban necessities, for example, biomass for heating, education facilities, settlements, recreation, tourism, and employment apply different pressures on the forest.
Keywords: 13. Climate action; 11. Sustainability; 15. Life on land